Successful Pregnancies in Two Patients on Chronic Haemodialysis - Coşkun, Ayhan; Kıran, Gürkan; Özdemir, Özgür; Köstü, Bülent; Doğan, Ekrem (Gynecology Obstetrics & Reproductive Medicine, 2007)
To discuss two pregnants with end stage renal failure. Two pregnancies delivered successfully during 37th and 38th weeks of pregnancy. Chronic renal failure patients who required dialysis can rarely become pregnant. Although there are some improvements in recent years, fetal survival is still about 50% in these patients. Most common complications are hypertension, polyhydramnios, and preterm labor. Spontaneous delivery occurs at an average of 32nd gestational week. Prematurity due to preterm labor is still the most common reason for neonatal mortality. Polyhydramnios can be prevented by increasing the dialysis dose and so duration of gestation can be prolonged and fetal survival improves. Because of two dialysis patients managed in our hospital, we aimed to investigate the recent data about chronic renal failure patients that required dialysis during pregnancy.